Institutionalizing early vaccination of newborns delivered at government health facilities: Experiences from India - Taneja, Gunjan; Kiran Mentey, Vijaya; Jain, Manish; Singh Sagar, Karan; Tripathi, Bhupendra; Favin, Micheal; Steinglass, Robert (International Journal of Medical Research and Review, 2015)
Newborn Vaccination is identified as a critical parameter for evaluating the overall performance of immunization programs with guidelines clearly advocating for administration of BCG, OPV zero dose and Hepatitis B birth dose to newborns. However in spite of sustained improvement in full immunization coverage in India, coverage of newborn vaccines has remained traditionally low. The USAID supported Maternal and Child Health Integrated Program (MCHIP), operational in India from 2009 – 2014 provided technical support to the Universal Immunization Program (UIP) at the National level and in the states of Jharkhand and Uttar Pradesh. During the project period, MCHIP undertook an assessment in 46 selected health facilities across 5 districts of the two states to study the implementation of the newborn vaccination program. Key findings from the assessment included a lack of knowledge among staff about the benefits of newborn vaccination, absence of written guidelines, unavailability of one vaccine compromising the administration of the remaining two and poor documentation practices. Following the assessment technical support was provided to strengthen implementation at these selected facilities which included providing on-the-job orientations to staff members posted in delivery rooms, establishing a sound supply chain mechanism to ensure round the clock availability of vaccines in labour rooms, strengthening documentation by incorporating separate columns in the delivery registers for recording vaccine administration and improved Supportive Supervision mechanisms. The intervention produced favorable results with a progressive increase in coverage of not only BCG and OPV zero dose but also Hepatitis B birth dose which was introduced in the UIP during the course of the intervention. Overall this intervention, which focused on operationalizing an already existing strategy, clearly indicated that the practice of vaccinating newborns delivered at health facilities is easily implementable and replicable, and that its sustainability should ensure improved coverage and protection against targeted vaccine-preventable diseases.